Enhancing biomass and lipid productions of microalgae in palm oil mill effluent using carbon and nutrient supplementation - Cheah, Wai Yan; Show, Pau Loke; Juan, Joon Ching; Chang, Jo-Shu; Ling, Tau Chuan (Elsevier, 2018)
Microalgae are a promising feedstock for biofuel generation. Economical and effective mass cultivation is essential for greater feasibility in microalgal-based biofuel full applications. The present study reported on cultivation of Chlorella sorokiniana CY-1 in palm oil mill effluent (POME) under photoautotrophic and mixotrophic cultivation. Enhancement of biomass and lipid productions were carried out by using glucose, urea and glycerol supplementations. Mixotrophic cultivation was more effective than photoautotrophic condition. Glycerol addition exhibited greater microalgae growth performance compared to supplementing glucose or urea. Biomass (1.68 g L−1) and lipid (15.07%) production were highest in POME medium with combinations of 200 mg L−1 urea, glucose and glycerol supplementation. Chlorella sorokiniana CY-1 grown in POME with glucose and glycerol supplementation gave considerably comparable yields as in all supplements-added POME medium. Ideal fatty acids compositions shown in urea and glycerol supplemented-POME medium though lower biomass production obtained. The pollutant remediation efficiencies attained were 63.85% COD, 91.54% TN and 83.25% TP in all supplements-added medium. The estimated net energy ratio was 0.55 and nutrient cost could be reduced up to 76%. Cheap and effective carbon and nutrients supplementation is essential to minimize the economic impact and maximize yields in commercial scale microalgae cultivation for biofuel production and environmental sustainability.